Rasionalitas Penggunaan Obat Antituberkulosis Pada Pasien Tuberkulosis Paru Rawat Jalan - Jeshy Milantika; Muhammad Akib Yuswar; Nera Umilia Purwanti (Journal Syifa Sciences and Clinical Research, 2022)
Tuberculosis is an infectious disease caused by the bacterium Mycobacterium tuberculosis. Tuberculosis is easily transmitted through the air or from a source of transmission, namely patients with positive AFB (acid-fast bacilli) tuberculosis when coughing or sneezing. The purpose of this study was to evaluate the rationale for using OAT in pulmonary TB patients and examine the relationship between gender, age, chronic comorbidities and duration of treatment with treatment outcomes. The method used in this research is descriptive observational method with a cross sectional design. The sample used was 60 people. Data collection was carried out retrospectively using medical record data and patient prescriptions in the outpatient installation of RSUD dr. Soedarso Pontianak for the period January-December 2020. The results showed that the rationality of using antituberculosis drugs in pulmonary TB patients based on the right indications was obtained by 100%, the right patient 100%, the right drug 96.7%, the right dose 85%, and the right time giving 95%.